74.7k views
1 vote
If g(x) = …… , what is the equation of the slant asymptote? ….

If g(x) = …… , what is the equation of the slant asymptote? ….-example-1
User Rik Schaaf
by
4.5k points

1 Answer

2 votes

We have the function g(x) defined as:


g(x)=(4x^2-7x)/(-x+2)

To find the slant asymptote, we must divide the numerator by the denominator:

Then, the slant asymptote is defined as the quotient of the division. We conclude that the equation of the slant asymptote is:


y=-4x-1

If g(x) = …… , what is the equation of the slant asymptote? ….-example-1
User Turner
by
5.2k points